Hepatoprotective Role of 4-Octyl Itaconate in Concanavalin A-Induced Autoimmune Hepatitis - Yang, Wenchang; Wang, Yaxin; Zhang, Peng; Wang, Tao; Li, Chengguo; Tong, Xin; Zeng, Xiangyu; Yin, Yuping; Tao, Kaixiong; Li, Ruidong (Mediators of Inflammation, 2022)
4-Octyl itaconate (OI) is a novel anti-inflammatory metabolite that exerts protective effects in many various disease models. However, its function in autoimmune hepatitis- (AIH-) associated hepatic injury has not been investigated. In this study, we successfully used concanavalin A (Con A) to establish an AIH-associated liver injury model. Furthermore, we investigated the effect of OI in Con A-induced liver injury and found that OI mitigated Con A-induced histopathological damage. OI administration reduced serum levels of alanine transaminase and aspartate transaminase in Con A-treated mice and attenuated the infiltration of macrophages induced by Con A. Moreover, OI effectively inhibited the expression of proinflammatory cytokines including interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), interferon-gamma (IFN-γ), and IL-1β induced by Con A. Furthermore, OI decreased hepatocyte apoptosis and malondialdehyde levels and increased the reduced glutathione/oxidized glutathione ratio in the Con A-induced liver injury model. In addition, we found that OI inhibited Con A-induced hepatocyte apoptosis in vitro, while Nrf2 deletion eliminated this effect. Furthermore, we administrated the Nrf2 inhibitor ML385 in OI+Con A-treated mice and found that ML385 eliminated the protective effect of OI in vivo. In addition, OI inhibited Con A-induced activation of nuclear factor-kappa B (NF-𝜅B) and the expression of proinflammatory cytokines in macrophages. Therefore, OI protected mice from Con A-induced liver damage and may be associated with Nrf2 activation and NF-𝜅B inhibition. Finally, our study revealed that OI inhibited TNF-α, or supernatants from Con A-treated RAW264.7 cells induced hepatocyte apoptosis. In conclusion, our study indicated that OI alleviated Con A-induced hepatic damage by reducing inflammatory response, oxidative stress, and apoptosis.